Use of nitric oxide as a strategy for postharvest controlling blue mold in 'Cripps Pink' apples - Gularte P.S.* (2023)
© 2023 International Society for Horticultural Science. All rights reserved.Blue mold, caused by Penicillium expansum, is responsible for considerable economic losses during the storage and marketing of apples. The aim of the present study was to evaluate the effect of nitric oxide (NO) on the blue mold and ripening of 'Cripps Pink' apples. Fruit were placed in hermetically sealed glass jars and injected with 0, 5, 10, 50 or 100 μL L-1of NO. Fruit were exposed daily to NO for 2 h in normal atmosphere. Apples were either inoculated (for blue mold evaluation) with 10 μL of P. expansum spore suspension (106 spores mL-1) or left untreated [for ripening assessment (flesh firmness, background skin color and titratable acidity)]. Fruit remained under ambient conditions (21±1°C and 63±5% RH) for 7 (inoculated apples) and 14 (uninoculated apples) days of shelf life. The experiment was carried out using a completely randomized design, with four replications of 10 apples. NO applications of 10, 50 and 100 μL L-1reduced the severity of blue mold in 'Cripps Pink' apples and had a higher flesh firmness and titratable acidity than the 0 and 5 μL L-1NO treatments. There was no effect of NO application on the background skin color. The postharvest application of nitric oxide may be a viable alternative for the control of blue mold and delay ripening of 'Cripps Pink' apples.